2021
DOI: 10.3389/fgene.2021.686116
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circRNA Biomarker for Acute Myocardial Infarction Based on System Biological Analysis of RNA Expression

Abstract: Acute myocardial infarction (AMI) is myocardial necrosis caused by the persistent interruption of myocardial blood supply, which has high incidence rate and high mortality in middle-aged and elderly people in the worldwide. Biomarkers play an important role in the early diagnosis and treatment of AMI. Recently, more and more researches confirmed that circRNA may be a potential diagnostic biomarker and therapeutic target for cardiovascular diseases. In this paper, a series of biological analyses were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…ROC curve analyses showed that circRNA_104761 had high sensitivity and specificity. These findings suggested the possible diagnostic role of circRNA_10476 in AMI ( Yang et al, 2021 ).…”
Section: Clinical Significance Of Circular Rnas In Myocardial Infarctionmentioning
confidence: 78%
See 2 more Smart Citations
“…ROC curve analyses showed that circRNA_104761 had high sensitivity and specificity. These findings suggested the possible diagnostic role of circRNA_10476 in AMI ( Yang et al, 2021 ).…”
Section: Clinical Significance Of Circular Rnas In Myocardial Infarctionmentioning
confidence: 78%
“…Notably, circRNA_104761 was revealed to sponge microRNA-449 and microRNA-34a that is relevant to AMI ( Fan et al, 2013 ; Zhang M. et al, 2019 ). In a larger cohort, circRNA_104761 levels were the lowest in AMI patients and highest in healthy coronary artery volunteers, suggesting the abundant expression of circRNA_104761 in human blood ( Yang et al, 2021 ). ROC curve analyses showed that circRNA_104761 had high sensitivity and specificity.…”
Section: Clinical Significance Of Circular Rnas In Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are produced by reverse splicing of the precursor mRNA transcript, in which the upstream splicing receptor connects to the downstream splicing donor ( 6 ). As an effective sponge of miRNA, circRNA interacts with miRNA to regulate mRNA expression ( 7 ). A large number of studies have demonstrated that circRNA is involved in the development of a variety of cardiovascular diseases, including heart failure ( 8 ), atrial fibrillation ( 9 ), diabetic cardiomyopathy ( 10 ), dilated cardiomyopathy ( 11 ), acute myocardial infarction ( 12 ), and myocardial ischemia-reperfusion injury ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are produced by reverse splicing of the precursor mRNA transcript, in which the upstream splicing receptor connects to the downstream splicing donor (6). As an effective sponge of miRNA, circRNA interacts with miRNA to regulate mRNA expression (7). A large number of studies have demonstrated that circRNA is involved in the development of a variety of cardiovascular diseases, including heart failure (8), atrial fibrillation (9), diabetic cardiomyopathy (10), dilated cardiomyopathy (11), acute Abbreviations: AMI, acute myocardial infarction; circRNA, circular RNA; lncRNA, long non-coding RNA; miRNA, microRNA; ncRNA, non-coding RNA; GEO, Gene Expression Omnibus; DERNA, Differential Expression RNA; PPI, protein-protein interaction; DEG, differentially expressed gene; PCI, percutaneous coronary intervention; CFs, cardiac fibroblasts; MRE, microRNA response element; RBP, RNA binding protein; ORF, open reading frames; GO, Gene Ontology; KEGG, Kyoto Encyclopedia of Genes and Genomes; BP, biological process; CC, cellular component; MF, molecular function; ROC, receiver operating characteristic curve.…”
Section: Introductionmentioning
confidence: 99%